EMBR-17. PINEOBLASTOMA SEGREGATES INTO MOLECULAR SUBTYPES WITH DISTINCT CLINICOPATHOLOGIC FEATURES: REPORT FROM THE RARE BRAIN TUMOR CONSORTIUM. Issue 2 (22nd June 2018) - Li, Bryan; Vasiljevic, Alexandre; Ho, Ben; Norman, Joseph; Lu, Mei; Hwang, Eugene; Hansford, Jordan; Jouvet, Anne; Laquerriere, Annie; Delisle, Marie-Bernadette; Gururangan, Sridharan; Fangusaro, Jason; et al.
Abstract: Pineoblastoma (PB) is a rare but aggressive pediatric brain tumour arising from the pineal gland. Outcomes remain dismal with long-term survival rates between 10–40% despite intensive treatment regimens. Although germline RB1 and DICER1 alterations have been reported in a small proportion of PB, the clinical significance of such alterations and the biology of sporadic cases remains unknown. We undertook global methylation profiling of 75 PB cases, and discovered that PBs comprise four molecular sub-types, designated groups 1 to 4 with characteristic copy number alterations and mutational patterns. Molecular sub-groups of PB also exhibited distinct clinical features and survival outcomes. While PBs group 1–3 arose in older children (median ages 5.2–12.6 years), group 4 PB was restricted to much younger children (median age 1.4 years). Group 4 PB exhibited the highest incidence of metastases (53%) and had the worst 5-year event-free survival (EFS) and overall survival (OS), respectively 7.7% and 16.7%. In contrast, group 2 patients had a 5-year EFS and OS of 100%, while group 1 and 3 had intermediate outcomes (68.1%, 53.3% respectively). These findings demonstrate significant clinical and molecular heterogeneity in PB and underscore the critical need to define mechanisms underlying PB, so that precise patient stratification and selection of biology-informed therapies can be undertaken in future clinical trials.